Distinct gene expression profiles and regulation networks of nasal polyps in eosinophilic and non‐eosinophilic chronic rhinosinusitis. Issue 5 (16th January 2018) - Okada, Naoko; Nakayama, Tsuguhisa; Asaka, Daiya; Inoue, Natsuki; Tsurumoto, Tadao; Takaishi, Shinya; Otori, Nobuyoshi; Kojima, Hiromi; Matsuda, Akio; Oboki, Keisuke; Saito, Hirohisa; Matsumoto, Kenji; et al.
Abstract : Background: Chronic rhinosinusitis with nasal polyps (CRSwNP) is known to have 2 phenotypes in East Asia. Eosinophilic CRSwNP (ECRSwNP), defined as tissue eosinophilia and easily recurrent, is distinguished from other non‐eosinophilic CRSwNP (NECRSwNP) types. However, the pathogenesis of each remains unclear. Methods: Nasal polyp tissues from ECRS (ECRSwNP) and NECRS (NECRSwNP) patients were obtained, and their comprehensive gene expression profiles were investigated by microarray analysis. Bioinformatics approaches (eg, Ingenuity Pathway Analysis [IPA]) were used to interrogate the data sets. Results: Hierarchical clustering and principal component analysis (PCA) collectively showed that ECRSwNP and NECRSwNP had distinct gene expression patterns. Of note, these genes could be divided into 8 distinctive clusters having different expression patterns and functions. Upstream Regulator Analysis revealed that not only T‐helper 2 (Th2) and the eosinophilia–related molecules (interleukin 4 [IL4], IL5, and colony stimulating factor 2 [CSF2]) reported so far, but also cell cycle regulators (cyclin dependent kinase inhibitor 1A [CDKNA1] and cyclin D1 [CCND1]) and a tissue fibrosis–related molecule (transforming growth factor β [TGFβ]) were identified in ECRSwNP. On the other hand, mainly interferons (IFNs) and acute inflammatory cytokines (IL1 and IL6) were predicted as upstream regulators in NECRSwNP. Conclusion: These results are useful for understanding the molecular basis of the mechanisms of CRSwNP and point to new targets for developing specific biomarkers and personalized therapeutic strategies for CRSwNP.